EVIDENCE-BASED PRACTICE AMONG OCCUPATIONAL HEALTH NURSES IN INDONESIA: A QUALITATIVE DESCRIPTIVE STUDY - Albyn, Devanda Faiqh; Malaka, Tan; Roestam, Ambar W.; Rochmayanti (International Journal of Patient Safety and Quality, 2026)
Background: Evidence-based practice in occupational health nursing is essential for improving workplace safety and healthcare quality. However, its implementation remains inconsistent, particularly in complex industrial settings. This study aimed to explore nurses’ experiences, perceptions, and barriers in implementing evidence-based practice. Methods: A qualitative descriptive design was employed. Data were collected through semi-structured interviews with 12 occupational health nurses selected using purposive sampling based on predefined inclusion criteria. Participants had at least two years of experience in occupational health settings. Interviews were conducted online, audio-recorded, and transcribed verbatim. Data were analyzed using thematic analysis, and rigor was ensured through member checking, peer debriefing, and audit trails. Results: Three main themes emerged: positive perceptions toward evidence-based practice, barriers to implementation, and organizational support and training needs. Nurses demonstrated strong awareness of the importance of evidence-based practice for improving decision-making and workplace safety. However, implementation was hindered by time constraints, limited access to scientific resources, insufficient organizational support, and gaps in research competence. Participants emphasized the need for structured training, leadership support, and system-level infrastructure to facilitate practice integration. Conclusions:Although occupational health nurses exhibit positive attitudes toward evidence-based practice, its implementation is limited by multi-level barriers. Strengthening training, organizational support, and access to evidence is critical to enhance adoption and improve occupational health outcomes and care quality.